Some Remarks on Keeping the Author's Style in Translation (By the example work of Sadriddin Ayniy) - Babayeva Dilbar Xabibdjanovna (Genius Journals, 2022)
This article discusses the successes and failures of translating the works of the great Tajik and Uzbek poet-writer Sadriddin Aini through French into Russian, and how the Russian translator S.Borodin turned proverbs, parables, and realities, that the French translator V. Vuano also translated some articles in the original text, used by the author to represent some portraits of heroes, The methods of simulation and comparison, based on the "art of interpretation", have not been translated into French because of the lack of translation. As a result, it is stated that the author's style has been compromised and that the artistic and national color are not fully reflected.
Keywords: Translation; style; French Oriental scholars; real words